The "Libation Installations" of the Tombs at Ugarit - Pitard, Wayne T. (The Biblical archaeologist, 1994)
Did the ancient Syrian inhabitants of Ugarit "feed" their dead after interment? Over six decades after Claude Schaeffer began his grand excavations of this Late Bronze Age metropolis and port, his interpretations of its tombs continue to offer "libation installations" and other funerary accoutrements to the unwary. But the archaeological data no longer support Schaeffer's suppositions regarding an active cult of the dead. It's time to lay the funerary installations at Ugarit to rest.